Role of extended release quetiapine in the management of bipolar disorders - Rayan K Al Jurdi (Dove Medical Press, 2010)
Rayan K Al Jurdi1,2, Lena A Dixit1, Martha Sajatovic3 1Baylor College of Medicine, Department of Psychiatry, Houston, Texas, USA; 2South Central Mental Illness Research and Clinical Core, Department of Veterans Affairs, Houston, Texas; 3Department of Psychiatry, Case Western Reserve University School of Medicine, Cleveland, Ohio, USAAbstract: Atypical antipsychotics have become a widely utilized component of the bipolar disorder treatment armamentarium, with approximately 45% of bipolar patients prescribed atypicals. Over the last decade all atypical drugs except for clozapine have received a Food and Drug Administration (FDA) bipolar indication. In October 2008, the FDA approved quetiapine XR monotherapy for the treatment of acute depressive episodes of bipolar disorder and acute manic or mixed episodes in bipolar I disorder based on two placebo-control trials. Quetiapine was also approved as adjunct therapy with lithium and divalproex for the treatment of acute manic or mixed episodes as well as maintenance of bipolar I disorder. In contrast to immediate release quetiapine which may require a twice-daily regimen, the XR formulation is intended for once-daily administration. This drug profile of quetiapine XR will address chemistry, pharmacodynamics, pharmacokinetics, metabolism, safety and tolerability and clinical trials in bipolar disorder.Keywords: quetiapine XR, bipolar disorder